DASAR TEORI KEWENANGAN PENYIDIK MAUPUN PENUNTUT UMUM DALAM MENGHENTIKAN PERKARA PIDANA - Taufik Rahman (Universitas Airlangga, 2010)
Based on literature studies, theoretical based for discontinue prosecution in Indonesia is hard to found. However, in develop countries such as US, England or Australia, theoretical based for discontinue prosecution can be identified as first, “realistic prospect of conviction” and second “prosecution on the public interest” theories. These two theories actually can be found in reasoning for SP3, SKPP and article 32 section c Prosecution Act. The primary difference is, in Indonesia, the discontinuity of public prosecution (SP3 and SKPP) is not discretional. In matters when the decision for discontinue the case appears, it put the Public Prosecutor and the Police Officer on dilemmatic position. For example, on the case No.04/Pi.Pralan/2008/PT.SBY and No. 01/Pdt.Praper/2005/PN.Sby, the Police Officers which handle the case still “freeze” the case because they think there is no reasonable prospect of conviction. The same thing happens on the case No.14/Pid.Prap/2010/PN.JktSel.and No: 149/PID/PRAP/2006/PT.DKI, the Public Prosecutor think there is no reasonable prospect of conviction and they think the prosecution is not on the public interest. On these matters, we suggest that there should be comprehensive studies if we putthe discontinuity of prosecution as discretional of power. Furthermore, “reasonable prospect of conviction” or “prosecution on the public interest” should become guidance or theoretical based for discontinue prosecution in Indonesia.